Les scénarios de localisation des capitales, révélateurs des conceptions de l’unité nationale - Géraldine Djament-Tran (Confins, 2010)
The comparative study of the location of national capital cities is a problem of spatial analysis as well as a geopolitical issue, since the recurring scenarios reveal different political conceptions of national unity. Various scenarios are identified and graphically represented in this article, based more specifically on the debates in Italy in the second half of the 19th century and in Germany in 1991: the central capital, the border capital, the historical capital, the missionary capital and the hinge capital. They can serve, alone or combined, to explain the location of today’s capitals. In a second part, we investigate the links between territory and politics revealed by the location of a capital. The choice of a strong or a weak capital, of a new or an old city, of a large or a small one, of a single or a shared capital cannot be separated from the debate between centralism and federalism, and raises, in fine, the question of geographical determinism. The article argues in conclusion for a systematic study of the links between capital and nation building.